Counting the heads of the Hydra: the development of the early medieval commentary on Boethius’s Consolation of Philosophy - Godden, M; Jayatilaka, R (Brepols, 2011)
It is well known that the Carolingian royal family inspired and promoted a cultural revival of great consequence. The courts of Charlemagne and his successors welcomed lively gatherings of scholars who avidly pursued knowledge and learning, while education became a booming business in the great monastic centres, which were under the protection of the royal family. Scholarly emphasis was placed upon Latin language, religion, and liturgy, but the works of classical and late antique authors were collected, studied, and commented upon with similar zeal. A text that was read by ninth-century scholars with an almost unrivalled enthusiasm is Martianus Capella’s De nuptiis Philologiae et Mercurii, a late antique encyclopedia of the seven liberal arts embedded within a mythological framework of the marriage between Philology (learning) and Mercury (eloquence). Several ninth-century commentary traditions testify to the work’s popularity in the ninth century. Martianus’s text treats a wide range of secular subjects, including mythology, the movement of the heavens, numerical speculation, and the ancient tradition on each of the seven liberal arts. De nuptiis and its exceptionally rich commentary traditions provide the focus of this volume, which addresses both the textual material found in the margins of De nuptiis manuscripts, and the broader intellectual context of commentary traditions on ancient secular texts in the early medieval world.